2006
DOI: 10.1051/0004-6361:20054784
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of SS433 with the RXTE

Abstract: We present our analysis of the extensive monitoring of SS433 by the RXTE observatory collected over the period [1996][1997][1998][1999][2000][2001][2002][2003][2004][2005]. The difference between energy spectra taken at different precessional and orbital phases shows the presence of strong photoabsorption (N H > 10 23 cm −2 ) near the optical star, probably due to its powerful, dense wind. Therefore the size of the secondary deduced from analysis of X-ray orbital eclipses might be significantly larger than its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…The best-fit radial velocity curve for the combined sets of data shown in Figure 2 gives from the optical (Antokhina & Cherepashchuk 1987) and Xray (Antokhina et al 1992;Filippova et al 2006) light curves. We caution that our adopted value of K X is not conclusive and that the systemic velocity, g, is significantly different from the surrounding nebulosity and absorption features.…”
Section: Discussionmentioning
confidence: 99%
“…The best-fit radial velocity curve for the combined sets of data shown in Figure 2 gives from the optical (Antokhina & Cherepashchuk 1987) and Xray (Antokhina et al 1992;Filippova et al 2006) light curves. We caution that our adopted value of K X is not conclusive and that the systemic velocity, g, is significantly different from the surrounding nebulosity and absorption features.…”
Section: Discussionmentioning
confidence: 99%
“…6d,7d). Cherepashchuk et al (2005), based on the RXTE/ASM and Ginga data, and also Filippova et al (2006), based on the RXTE/PCA data, found that during the 'edge-on' precession phase the flux in the standard X-ray range is only 2 times smaller than at the phase of maximal opening of the funnel. We confirm this result: despite the fact that the jet and the inner parts of the funnel are obscured during the 'edge-on' phase, the observer sees a considerable X-ray flux.…”
Section: Power Spectrum At the 'Edge-on' Precession Phasementioning
confidence: 95%
“…The companion star is supposed to be centered at the (400, 0, 400) point (Filippova et al 2006), outside the computational domain, while a collapsed stellar remnant is situated at the jet base, i.e. at (60, 0, 60).…”
Section: Hydrodynamical Code Employedmentioning
confidence: 99%